Deep decarbonization of the Indian economy: 2050 prospects for wind, solar, and green hydrogen - Shaojie Song; Haiyang Lin; Peter Sherman; Xi Yang; Shi Chen; Xi Lu; Tianguang Lu; Xinyu Chen; Michael B. McElroy (iScience, 2022)
Summary: The paper explores options for a 2050 carbon free energy future for India. Onshore wind and solar sources are projected as the dominant primary contributions to this objective. The analysis envisages an important role for so-called green hydrogen produced by electrolysis fueled by these carbon free energy sources. This hydrogen source can be used to accommodate for the intrinsic variability of wind and solar complementing opportunities for storage of power by batteries and pumped hydro. The green source of hydrogen can be used also to supplant current industrial uses of gray hydrogen produced in the Indian context largely from natural gas with important related emissions of CO2. The paper explores further options for use of green hydrogen to lower emissions from otherwise difficult to abate sectors of both industry and transport. The analysis is applied to identify the least cost options to meet India’s zero carbon future.